Ineffectiveness of measures to protect children and adolescents in child abuse, analysis of processes of family courts of the superior court of justice of Tacna / 2009-2010 - Justo Valencia, Úrsula María (2015)
Objective: This research was conducted in order to determine the effectiveness of measures to protect children and adolescents that are issued in the Family Court of the Superior Court of Justice of Tacna, on child abuse, 2009-2010.Para it was established the following hypothesis: In the Family Court of the Superior Court of Justice of Tacna, measures to protect children and adolescents that are issued are ineffective to counter child abuse in the district Tacna 2009- 2010. Method: The research is a form of applied research, because it is aimed at the application of knowledge to the solution of a problem, as confronting theory with reality. It is also a kind of Socio Legal Research by the facts and relations of social order regulated by legal norms are studied and why is to determine the effectiveness of measures to protect children and adolescents that are issued in the Family Courts Superior Court of Justice of Tacna child abuse in 2009- 2010. It is a non-experimental (ex post facto) Description Design - Explanatory. For this purpose the information obtained through the application of the questionnaire, document analysis was considered; and the Certificate of Interview; as instruments for measuring the variables studied. Results: The data were tabulated and analyzed using charts and graphs. Once the phase of analysis and interpretation of the results matter research hypothesis was verified. Conclusions: The results allowed us to know that children and adolescents have been subjected to physical abuse (hitting, beating, kicking, shakings); they have also been subjected to sexual violence (attempted rape, improper touching, and rape). As psychological and emotional abuse: movement restrictions, the continued depreciation, guilt, threats, acts of terror, discrimination or ridicule were some of the abuses to which they were subjected. Finally, it must have been neglect or abandonment by their parents; They neglected as health, education, emotional development, nutrition, home and safe living conditions of children under study